Generation of a homozygous FIS1 knockout human embryonic stem cell line GIBHe015-B by CRISPR/Cas9 system - Mingquan Wang; Jun Tang; Tiancheng Zhou; Yuchan Mai; Yanling Zhu (Stem Cell Research, 2022)
The mitochondrial fission protein 1 (FIS1) is essential for mitochondrial division or fission and has been determined to mediate mitochondrial and peroxisomal fission. Other studies also found that FIS1 functions as an essential component of the mitophagy and apoptosis pathways in mammalian cells, suggesting that FIS1 has multiple important roles. Here, we generated homozygous FIS1 knockout human embryonic stem cells (hESCs) using the CRISPR/Cas9 system. This cell line exhibits normal karyotype, pluripotency, and trilineage differentiation potential, which could provide a useful cellular resource for exploring the functions of FIS1 and their implications in human health and diseases.